Financing the capital development of the economy: A Keynes-Schumpeter-Minsky synthesis - Mariana Mazzucato; Larry Randall Wray (Levy Economics Institute of Bard College, 2015)
This paper discusses the role that finance plays in promoting the capital development of the economy, with particular emphasis on the current situation of the United States and the United Kingdom. We define both "finance" and "capital development" very broadly. We begin with the observation that the financial system evolved over the postwar period, from one in which closely regulated and chartered commercial banks were dominant to one in which financial markets dominate the system. Over this period, the financial system grew rapidly relative to the nonfinancial sector, rising from about 10 percent of value added and a 10 percent share of corporate profits to 20 percent of value added and 40 percent of corporate profits in the United States. To a large degree, this was because finance, instead of financing the capital development of the economy, was financing itself. At the same time, the capital development of the economy suffered perceptibly. If we apply a broad definition-to include technological advances, rising labor productivity, public and private infrastructure, innovations, and the advance of human knowledge-the rate of growth of capacity has slowed. The past quarter century witnessed the greatest explosion of financial innovation the world had ever seen. Financial fragility grew until the economy collapsed into the global financial crisis. At the same time, we saw that much (or even most) of the financial innovation was directed outside the sphere of production-to complex financial instruments related to securitized mortgages, to commodities futures, and to a range of other financial derivatives. Unlike J. A. Schumpeter, Hyman Minsky did not see the banker merely as the ephor of capitalism, but as its key source of instability. Furthermore, due to "financialisation of the real economy," the picture is not simply one of runaway finance and an investment-starved real economy, but one where the real economy itself has retreated from funding investment opportunities and is instead either hoarding cash or using corporate profits for speculative investments such as share buybacks. As we will argue, financialization is rooted in predation; in Matt Taibbi's famous phrase, Wall Street behaves like a giant, blood-sucking "vampire squid." In this paper we will investigate financial reforms as well as other government policy that is necessary to promote the capital development of the economy, paying particular attention to increasing funding of the innovation process. For that reason, we will look not only to Minsky's ideas on the financial system, but also to Schumpeter's views on financing innovation.
Keywords: B5; B51; B52; G; G1; G2; H6; L5; N1; O1; O2; O3; O4; P1; 330; Banker as Ephor of Capitalism; Capital Development; Finance; Global Financial Crisis; Innovation; Minsky; Schumpeter